Marketing Mix on UINSU Students’ Buying Interest in Skintific Through Brand Image as A Moderating Variable - Sitorus, Nurbaina Junita; Syahriza, Rahmi; Aisyah, Siti (Yayasan Sinergi Kawula Muda, 2024)
This research aims to determine the effect of the marketing mix (4P) on North Sumatra State Islamic University (UINSU) students' buying interest in Skintific products, with brand image as a moderating variable. This research is a type of comparative causal research with a quantitative approach because it involves numerical data and uses statistical data. The population in this study are active female students studying at the North Sumatra State Islamic University (UINSU) with a population of 17,608 female students in 2023. Using the Slovin formula n= N/ (1+ (N x e2 )) to calculate the sample size so that a sample of 103 respondents was obtained. Sampling was carried out using the probability sampling method because it can obtain a representative sample that accurately reflects the target population. Primary data in this research was obtained from a questionnaire with 27 questions to measure marketing mix variables, purchase interest and brand image using a five-point Likert scale which was distributed online via Google Form. Data analysis used in this research is IBM SPSS which includes normality test, multicollinearity test, path analysis (path analysis), and hypothesis testing. The research results show that the marketing mix (4P) has a significant effect on consumer buying interest, and brand image moderates this relationship. These findings highlight the importance of effective marketing strategies and a strong brand image to increase consumer interest and loyalty.